Applying recent developments in time series econometrics to the spatial domain. - Stern, David I. (Professional Geographer, 2000)
The writer assesses recent developments in time series econometrics and examines the applicability of these developments to purely spatial and spatio-temporal data. He notes that previous vector autoregression models and methodology had purely spatial analogs, but similar to the case of traditional regression models, application of the methods will be more problematic in the spatial domain. He develops space-time cointegration and Granger causality methods and uses them to explain reductions in sulfur emissions in Europe.